Paleomagnetism of Late Proterozoic rocks, Victoria Island, Northwest Territories, Canada - Palmer, H. C.; Baragar, W. R. A.; Fortier, M.; Foster, J. H. (Canadian Journal of Earth Sciences, 1983)
Late Proterozoic Natkusiak plateau basalts and associated dolerite dikes and sills of Victoria Island show paleomagnetic polarities that relate them to the Franklin diabases but are complicated by the effects of a downward component that cannot be wholly removed in all sites by AF and thermal demagnetization. In a preserved thickness of about 740 m of Natkusiak flows the polarity changes upward in roughly successive thirds of the section from east and slightly downward (reverse), to west and slightly downward (normal), to east and slightly upward (reverse). Thus there is a double reversal in the section but the lower reverse direction is badly contaminated by a downward directed overprint. At three sites this steep downward component persists after cleaning. Dolerite polarities, except for one that is normal, cluster in the east-down (reverse) direction close to the lower reverse direction of the lavas and steeply downward, similar to the overprint direction in the flows. The downward component can be correlated with evidence of low initial oxidation and more severe alteration in the corresponding samples and may be related to burial metamorphism. The reverse direction of the upper lavas, being from the freshest parts of the section and closest in direction to the exact reversals recorded in Franklin dikes from Baffin Island, is believed to be most reliable. Paleopole positions are: upper reverse lavas, 161°E, 2°N; middle normal lavas, 159°E, 9°N; combined middle–upper lavas, 159°E, 6°N (δp = 4°, δm = 8°).Reynolds Point shales from the Shaler Group underlying Natkusiak basalts and host to the dolerite sills yielded a paleopole position at 147°E, 6°S, significantly removed from the Franklin poles but probably not indicative of an age greater than Hadrynian.